7m+6-8m=36

Simple and best practice solution for 7m+6-8m=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m+6-8m=36 equation:


Simplifying
7m + 6 + -8m = 36

Reorder the terms:
6 + 7m + -8m = 36

Combine like terms: 7m + -8m = -1m
6 + -1m = 36

Solving
6 + -1m = 36

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1m = 36 + -6

Combine like terms: 6 + -6 = 0
0 + -1m = 36 + -6
-1m = 36 + -6

Combine like terms: 36 + -6 = 30
-1m = 30

Divide each side by '-1'.
m = -30

Simplifying
m = -30

See similar equations:

| 12v^2+23v-24=0 | | 2-x=-22 | | (2x+6)+(2x+5)+(2x)=(2x)+(2x)+(3x+6) | | n-mn=4k+3 | | 6x+7x-76=38-6x | | 0=12x-3y | | -38=5(x-7)-8x | | 15y^3-25y^2=0 | | 8=3+6 | | 7x-192=-3x+56 | | 2+y^3=-1 | | 5(1-7a)+6(1-2a)=11 | | 6y+9=3(2-d) | | -6(3x-2)=5 | | x-46=-63 | | 5y+3y-2y=48 | | 25=9x+5-5x | | 3(5x-3)-6x=3(3x+2) | | 72+40=36+x | | 21+25m=28+18m | | 3y-6=2x+4 | | 13-17+24= | | 36-(2x+4)=2(x+6)+x | | 10-2(y-7)=3y+9 | | 150+20x=60+38x | | 32+x=-15 | | -(p+1)+5(p+8)=47 | | X+1.7=1.7x+22.9 | | 5-3(4x+3)=2 | | -(-2n-4)=5(n+2) | | 36=-9(10+1) | | 23=14+4n |

Equations solver categories